Factors Impacting Customers’ Satisfaction, Loyalty, and Continuance Intention in Using Car Sharing Service Platform in Chengdu, China - Jiang, Junpeng (Scholar: Human Sciences, 2024)
Purpose: By understanding the importance of commitment, satisfaction, and continuance intention, service providers can enhance their strategies for delivering these benefits to customers, ultimately fostering customer loyalty. This study aims to examine factors impacting customers’ satisfaction, loyalty, and continuance intention to use car-sharing services platforms. The key variables include perceived ease of use, perceived usefulness, perceived quality, value for money, commitment, satisfaction, customer loyalty, and continuance intention. Research design, data, and methodology: The researchers employed a quantitative method, using online survey distributed to 500 respondents in the Chengdu region of China. The data collected from the survey was then analyzed using confirmatory factor analysis, and structural equation modeling to test the research hypotheses. Results: Perceived ease of use has a significant impact on perceived usefulness. Perceived ease of use and perceived usefulness significantly impact satisfaction, and continuance intention. In addition, perceived quality and value for money significantly impact satisfaction. Lastly, commitment and satisfaction positively impact customer loyalty. Conclusions: This study provides initial insights into the factors contributing to customers' decision to stay in peer-to-peer relationships within the sharing economy. Furthermore, the study suggests how service providers can strengthen the relationships between customers and peer service providers.